Climate-influenced cave deposition and human occupation during the Pleistocene in Zhiren Cave, southwest China. (10th September 2020) - Ge, Junyi; Deng, Chenglong; Wang, Yuan; Shao, Qingfeng; Zhou, Xinying; Xing, Song; Pang, Haijiao; Jin, Changzhu
Abstract: A large number of hominin fossil-bearing caves in South China have yielded evidence for the occupation of early modern humans during the Middle to Late Pleistocene. However, the geology of these caves and the paleoenvironmental context of human occupation remain poorly documented and understood. In this study, we obtained new ages yielded by MC-ICPMS uranium-series dating of speleothems from Zhiren Cave, Guangxi, where a partial early modern human mandible and 2 M have been recovered. The ages demonstrate that cave infilling of Zhiren Cave began at ~1 Ma, much earlier than the date previously suggested. Our dating results also suggest that fossils of anatomically modern human were deposited in Zhiren Cave during marine isotope stage (MIS) 6, between ~190 and ~130 ka, representing the oldest known anatomically modern human remains in East Asia. The cave's sedimentary processes and the paleoenvironmental changes were reconstructed based on detailed analyses of lithostratigraphy, grain-size, pollen assemblages and the chemical weathering intensity of the sediments inside Zhiren Cave. The results show that major climatic changes in the Middle Pleistocene led to the accelerated incision of local streams and the erosion of cave sediments by controlling the regional hydrological response during the Early to Middle Pleistocene. After ~300 ka, increased climatic contrasts between glacial and interglacial periods dominated the accumulation of sediments and the occupation of mammals and early modern humans in Zhiren Cave. Gradually desiccating climatic conditions and reduced forest cover during the penultimate glacial period (MIS 6) may have define a temporal window for the human occupation of Zhiren Cave, providing ideal environmental conditions. However, floodwater incursion and/or dense vegetation cover corresponding to a much warmer and wetter climate in the subsequent last interglacial (MIS 5) may have discouraged humans from further occupying Zhiren Cave.